2011
DOI: 10.1097/mlr.0b013e318223a9f1
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Staffing and Patient Care Costs in Acute Inpatient Nursing Units

Abstract: The association of nurse staffing level with costs per admission differed for medical versus surgical admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 18 publications
1
25
0
1
Order By: Relevance
“…The better patient outcomes associated in this study with richer skill mix suggest that, as in the USA where detailed cost information is available, fewer expensive complications like infection, shorter length of stay and fewer intensive care unit days among patients in hospitals with better professional nurse staffing would likely offset higher labour costs associated with richer skill mix and return good value to health systems. 26 Our results of one of the first comprehensive studies of nursing skill mix in Europe are similar to results obtained in studies of nursing skill mix in the USA. Our four state study in the USA showed 30-day general surgery mortality rates of 1.2% 32 compared with European in-hospital mortality rates shown here of 1.28%; the US patients studied included all adult patients aged 20-85 years while the European patients were aged 50 years and older.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The better patient outcomes associated in this study with richer skill mix suggest that, as in the USA where detailed cost information is available, fewer expensive complications like infection, shorter length of stay and fewer intensive care unit days among patients in hospitals with better professional nurse staffing would likely offset higher labour costs associated with richer skill mix and return good value to health systems. 26 Our results of one of the first comprehensive studies of nursing skill mix in Europe are similar to results obtained in studies of nursing skill mix in the USA. Our four state study in the USA showed 30-day general surgery mortality rates of 1.2% 32 compared with European in-hospital mortality rates shown here of 1.28%; the US patients studied included all adult patients aged 20-85 years while the European patients were aged 50 years and older.…”
Section: Discussionsupporting
confidence: 84%
“…[21][22][23][24] The US studies have generally concluded that a hospital skill mix with proportionately more professional nurses yields greater value because higher wages of professional nurses are offset by reductions in length of stay, lower use of intensive care, fewer costly adverse events such as hospital-acquired infections and lower readmission rates. [25][26][27][28][29] Needleman et al estimated that holding constant the total number of hours of nursing care provided, replacing lower qualified licensed practical nurses with fewer years of education with professional nurses would result in lower hospital mortality, shorter length of stay, fewer complications and net savings. 30 The aim of this paper is to inform managerial and policy decision-making about hospital nursing skill mix in Europe through an analysis of the association between nursing skill mix and patient mortality, patient ratings of their care and quality of care indicators in hospitals in six European countries: Belgium, England, Finland, Ireland, Spain and Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…2009, Li et al . 2011, Weiss et al . 2011), one was a meta-analysis of observational studies (Kane et al .…”
Section: Resultsmentioning
confidence: 99%
“…Li et al . (2011) estimated the contribution of nursing costs to inpatient costs to calculate the change in cost for a one unit change in the staffing variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation